Branding Coffe Shop With Islamic Values As Marketing Communication Strategy Across Social Media Platform - Thalitha Sacharissa Rosyiidiani; Aurelia Syafira Widya (Journal Research of Social Science, Economics, and Management, 2021)
Business in the food and beverage industry in Indonesia is growing every year. The sector also makes a significant contribution so that it can increase economic growth in Indonesia. Apart from cafes, coffee shops are one of the most desirable parts of the culinary industry today. Very significant business development is currently happening in the coffee shop industry, which appears in big cities. Al'Cal Coffee is a business engaged in the F&B industry, especially coffee shops. Al'Cal is an Islamic coffee shop founded in 2018 and successfully opened a second branch in Serpong in September 2020. In running its business, each coffee shop must have different marketing communication strategies and activities. This study aims to identify the marketing communication activities carried out by Al'Cal Coffee on Instagram, how Al'Cal Coffee implements the integrated marketing communication strategy, and the Islamic elements contained in Al'Cal Coffee's marketing communication strategy Instagram. This study uses a qualitative descriptive method with primary data from interviews, observations, and documentation. The study results illustrate that there is a match and relationship between the theory of Integrated Marketing Communication Strategy with those in the field. The strategy is carried out starting from the planning, implementation, and evaluation stages.